Metaphysics - Van Inwagen, Peter (Dimensions of philosophy series, 1993)
Metaphysics is a branch of philosophy that attempts to answer the deepest questions about how things really are. The author builds his textbook around these crucial questions: what are the most general features of the world; why does the world exist and what is the nature of rational beings and their place in the world. This text surveys the traditional answers to these questions and shows by example how to think about them more clearly and deeply on one's own. It introduces most of the perennial topics of metaphysics, including appearance and reality, identity and individuation, objectivity, necessary existence of mind and body, teleology and freedom of the will.